Linguocultural features of national foods in the English and Uzbek languages - Olimova, Kamolat Hamid qizi; Khaitkulov, Zakhriddin Khazratkul ugli (The Lingua Spectrum, 2026)
This study examines the linguocultural features of national food names in English and Uzbek through comparative lexicological and ethnolinguistic analysis. Food terminology functions as a cultural artifact reflecting national identity, social norms, and historical narratives. The research demonstrates that English culinary nomenclature predominantly employs descriptive compositional patterns emphasizing clarity and functionality, while Uzbek dish names exhibit morphological richness through derivational suffixes and culturally embedded semantics. English food idioms reflect individualistic pragmatism, whereas Uzbek culinary expressions encode collectivist values, hospitality, and kinship. The sacred status of bread in Uzbek culture contrasts with the utilitarian perception in English-speaking societies. Globalization triggers lexical borrowing in both languages, yet Uzbek maintains stronger ties to agrarian traditions. These findings contribute to cross-cultural understanding, translation studies, and intercultural communication pedagogy. Furthermore, the study highlights the role of culinary vocabulary in preserving intangible cultural heritage and demonstrates how food-related expressions serve as linguistic markers of worldview, tradition, and social interaction across generations in both linguistic communities.